Developing of English paragraph writing ability using the process Approach of second year students, Faculty of Languages, Souphanouvong University, Luangprabang, Lao PDR. - BOUNTHAVONG, Oudalon; PHOMMASENG , Sisoury; MEKSAVANH, Somechay (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The purpose of this research were to study and compare the English paragraph writing ability of second year students before and after learning using the Process Approach and to study the students’ attitude towards teaching English paragraph writing using the Process Approach. The sample consisted of 29 second year students who enrolled in English writing courses in the first semester of the academic year 2018-2019 of Faculty of Languages, Souphanouvong University selected by cluster random sampling. The design of this research was a one group pretest-posttest design. The research instruments were 6 lesson plans, and English paragraph writing ability test and a students’ attitude questionnaire. The experiment performed 6 weeks, 3 hours a week, 18 hours in total. The mean, percentage, standard deviation and t-test for dependent sample using SPSS for windows computer programme were used to analyze data. The findings of this research were as follows: The students’ pretest score on English paragraph writing ability was 48.70 percent and the posttest was 75.03 percent. The mean score on the posttest was higher than that of the pretest. The students’ English paragraph writing ability was significantly different at the .01 level. The students’ attitude toward teaching English paragraph writing using the Process Approach was at a good level.